Canadian Consensus Guidelines for the Optimal Use of Etravirine in the Treatment of HIV-Infected Adults. Issue 2 (2009) - Harris, Marianne; Angel, Jonathan B; Baril, Jean-Guy; Rachlis, Anita; Trottier, Benoit
Abstract : BACKGROUND AND OBJECTIVES: A group of five Canadian physicians with significant experience in HIV management was convened. Their goal was to develop guidance specifically for Canadian HIV-treating physicians on the appropriate use of etravirine (TMC125, Intelence, Tibotec BVBA, Belgium) in adult HIV-infected patients. METHODS: Evidence from the published literature, conference presentations and expert opinions of the group members were used to develop the recommendations. Feedback on the draft recommendations was obtained from this core group, and from seven other physicians across Canada with clinical HIV treatment expertise and experience in the use of etravirine, as well as two Canadian scientists with HIV expertise. The final recommendations represent the core group's consensus agreement, taking all feedback into consideration. RESULTS AND CONCLUSIONS: The recommendations were developed to guide physicians in the optimal use of etravirine. The issues considered included HIV disease status, antiretroviral treatment history, drug resistance profiles, predictors of response to etravirine, background antiretroviral regimen and drug-drug interactions.